Issues of Improving the Legislation of The Republic of Kazakhstan Based on The International Standards on Counteraction to Crimes Connected with Human Trafficking - LEONOV, Denis; AYAGANOVA, Sagynysh (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).29, 2018)
Rationale : The relevance of the research is due to the fact that now, both in the territory of Kazakhstan and all over the world, some changes and reforms in the social, economic and political spheres take place, which contributes to the growth of transnational organized crime. In this regard, the mechanisms for protection of human life, rights and freedom require an increased efficiency, improvements in criminal legislation and the quality of justice. Purpose of the study: The purpose of the study is to identify potential gaps, to develop scientifically-based proposals for improving the legislation on the basis of international standards and foreign experience. Methods: The basic methods of studying the problem were analysis and comparison, which allowed studying the problem by identifying differences and similarities among the laws of different countries and identifying the positive aspects that could be introduced into the laws of Kazakhstan. The comparative analysis of criminal legislation of foreign countries allows concluding that the unification of legal norms in the sphere of counteraction to crimes connected with human trafficking is necessary, as the effectiveness of combating this category of crimes is due to the effectiveness of the state's implementation of international standards in this area. Results: The presented research was carried out taking into account the Kazakhstan's criminal policy and international legislation, which resulted in the advancement of reasonable proposals for amendments and additions to the criminal legislation on the tightening and criminalization of certain crimes related to human trafficking. Significance of the results : The theoretical significance is related to the scientific comprehension of the complex reality of modern time, the most widespread form of transnational crime – human trafficking. The practical significance of the study is that the proposed provisions are aimed at improving national legislation that promotes quality counteraction to human trafficking.